Penggunaan Quizizz Paper Mode pada Model Pembelajaran Kooperatif Tipe Teams Games Tournament untuk Meningkatkan Keterampilan Kolaborasi dan Hasil Belajar Siswa - Hamida, Nazlafatin; Permatasari, Carolina Lita (Universitas Nusantara PGRI Kediri, 2026)
The ability to work together in a team or what is commonly called collaboration skills is very important for school students in the 21st century. Critical thinking, communication, collaboration and creativity are competencies contained in the 4C skills. The research method used is a type of classroom action research. The purpose of this study is to improve collaboration skills and student learning outcomes in Natural and Social Sciences subjects through a cooperative learning model of the Teams Games Tournament type using quizizz paper mode. The research subjects were fourth grade students of Salatiga 12 Elementary School through this type of classroom action research. Collaboration skills questionnaires in the form of self-assessment and written tests at the end of learning are the methods used to obtain data. The results of the study indicate that improving collaboration skills can help improve student learning outcomes in following learning which can be seen by looking at the average results of student learning in the pre-cycle of 62.1% and an increase in the average ability of student collaboration skills from 79% in cycle I to 97% in cycle II. So it can be concluded that the use of quizizz paper mode in the cooperative learning model of the Teams Games Tournament type can help improve collaboration skills and student learning outcomes.